Betrayal – Vice or Virtue? An Ethical Perspective on Accuracy in Simultaneous Interpreting - G. Seeber, Kilian; Zelger, Christian (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractSimultaneous conference interpreting represents a highly complex linguistic task and a very delicate process of information transfer. Consequently, the notion of truth – which applied to the field of simultaneous interpreting entails an accurate rendition of the original message – is of pivotal importance. In spite of that, an analysis of experimental transcripts and corpora sometimes seems to suggest that interpreters betray the speaker by deliberately altering the original. While we cannot exclude that such instances do exist, we argue that sometimes what looks like betrayal may in fact be a rendition based on a sound ethical decision. In this paper we take a closer look at these situations in an attempt to shed more light on the potential motivations underlying the interpreter’s decisions and actions. Using examples from real life interpreting situations, we take the interpreter’s output and put what at first sight appears to be a betrayal of the speaker on the ethical test bench, both from a deontological and a teleological perspective. Based on this analysis we propose a model suggesting that the interpreter uses three principal message components, verbal, semantic and intentional, in order to come up with an accurate interpretation of the original, which we call “truthful rendition.”